Survey of Forensically Important Calliphoridae in Samsun - Kökdener, Meltem; Polat, Erdal (The Bulletin of Legal Medicine, 2016)
Objective: This study was conducted from June 2009 to 2010 in north of Turkey, province Samsun. The objective was to determine forensically important Calliphoridae (Diptera) species and their seasonal distribution on dog carrcass during one year, this studies were carried out in a three different area of Samsun. Material and Methods: Three dogs carcass (Canis lupus familiaris L.), weighing approximately 15-20 kg each, were used as models for studying decomposition and insect succession in each experiments. Ambient daily temperature (maximum and minimum), relative humidity (RH) were recorded and existing keys were used for identification of different species. Results: Lucillia sericata (Meigen), Chrysomya albiceps (Wiedemann), Calliphora vomitoria (Linnaeus) and Calliphora vicina (Robineau-Desvoidy) species were encountered. It was shown that the seasonal distribution of the collected species was different from each other. Chrysomya albiceps was observed in summer, auntumn and spring. In the spring and winter, the dominant fly species were Calliphora vicina. The rate of carcass’s decomposition was faster in summer and autumn as compared to spring and winter. Results indicated that ambient temperature is the chief factor determining the seasonal variations in decay rate. Conclusion: This report also identified some of the Calliphoridae that occur in north of Turkey. The importance of regional faunistic studies of the calliphoridous community, the results of which may be applied to forensic practice in the future. Keywords: Forensic entomology, insect succession, corpse, postmortem interval, decomposition.